Surface modification of polymer textile biomaterials by N2 supercritical jet: Preliminary mechanical and biological performance assessment. (July 2020) - Khoffi, F.; Khalsi, Y.; Chevrier, J.; Kerdjoudj, H.; Tazibt, A.; Heim, F.
Abstract: Foreign Body Reaction (FBR) is a critical issue to be addressed when polyethylene terephthalate (PET) textile implants are considered in the medical field to treat pathologies involving hernia repair, revascularization strategies in arterial disease, and aneurysm or heart valve replacement. The natural porosity of textile materials tends to induce exaggerated tissue ingrowth which may prevent the implants from remaining flexible. One hypothesized way to limit the FBR process is to increase the material surface roughness at the yarn level. Supercritical N2 (ScN2 ) jet particle projection is a technique that provides enough velocity to particles in order to induce plastic deformation on the impacted surface. This work investigates the influence of ScN2 jet projection parameters like standoff distance or particle size on the roughness that can be obtained on medical polymer yarns of various diameters (100 and 400 μm) and woven textile surfaces obtained from a 100 μm yarn. Moreover, the mechanical and biological performances of the obtained modified textile material are assessed. Results bring out that with appropriate testing conditions (500 bars jet/500 mm distance between nozzle and PET textile) and particle size around 50 μm, it is possible to generate 20 μm large and 4 μm deep craters on a 100 μm monofilament PET yarn and fabric. Regarding the strength of the textile material, it is only slightly modified with the treatment process, as the tenacity of the yarns decreases by only 10%. Moreover, It is shown that the obtained structures tend to limit the adhesion and slow down the proliferation of human fibroblasts.